Study on the Efficiency Improvement of Cherenkov Detectors Using Colloids (2025)
Cherenkov detectors are widely used in experiments focused on cosmic ray detection. While ultrapure water is typically employed as the transparent medium, alternative media could be explored to improve their efficiency. This work investigates the use of a TiO2 colloid as an alternative to water for improve the detector’s performance. A Cherenkov detector was modeled in Geant4, considering only the refractive index of the medium, and received as input the muon flux simulated for the city of Medellín using CORSIKA. The preliminary results indicate that the use of TiO2 colloids improve the efficiency of the detector, specifically in the UV range, offering a potential approach for the improvement of Cherenkov detectors. Although these findings are promising, further work is needed to incorporate additional optical properties of the media for more ealistic and comprehensive results, as well as considering the long-term stability of the colloid.